Sustainable Shipping in a Changing Arctic (WMU Studies in Maritime Affairs, 2018)
This volume brings together multiple perspectives on both the changing Arctic environment and the challenges and opportunities it presents for the shipping sector. It argues for the adoption of a forward-looking agenda that respects the fragile and changing Arctic frontier. With the accelerated interest in and potential for new maritime trade routes, commercial transportation and natural resource development, the pressures on the changing Arctic marine environment will only increase. The International Maritime Organization Polar Code is an important step toward Arctic stewardship. This new volume serves as an important guide to this rapidly developing agenda. Addressing a range of aspects, it offers a valuable resource for academics, practitioners, environmentalists and affected authorities in the shipping industry alike.